2022
DOI: 10.1002/essoar.10510412.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simultaneous creation of a large vapor plume and pumice raft by a shallow submarine eruption

Abstract: The August 12, 2021 eruption of Fukutoku-Okanoba, a shallow submarine volcano in the Izu-Bonin arc of Japan, is one of few documented submarine eruptions to make a large aerial plume and floating pumice raft. Relative to past eruptions, this event was well-covered by multiple high resolution satellite remote sensors. Here we use satellite remote sensing to assess the eruption style, rates, and products. We find that the 16 km plume was water-rich. Furthermore, we conclude that the 0.1 kmˆ3 raft and 16 km plume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Together these observations lead to questions about the causes of these two eruptive pulses. In this context, one of the goals of this study is to provide a foundational timeline against which other future data sets 5,36 (e.g., seismic) can be compared to build a more complete picture of eruptive processes.…”
Section: Discussionmentioning
confidence: 99%
“…Together these observations lead to questions about the causes of these two eruptive pulses. In this context, one of the goals of this study is to provide a foundational timeline against which other future data sets 5,36 (e.g., seismic) can be compared to build a more complete picture of eruptive processes.…”
Section: Discussionmentioning
confidence: 99%
“…and marine organisms across thousands of kilometers, potentially dispersing nutrients and increasing microbial biomass and biodiversity in areas geographically distant from the site of the eruption (DeVantier, 1992;Risso et al, 2002;Bryan et al, 2012). Pumice rafts can also be a significant hazard for human maritime activities, especially by clogging harbors and affecting near shore sea life and fisheries, disrupting local economies (Bryan et al, 2012;Jutzeler et al, 2020), as observed in the recent raft dispersal from the 2021 eruption of Fukutoku-Okanoba volcano, a submarine volcano in the Bonin Arc (24.285 °N, 141.481 °E) (Fauria et al, 2022;Yoshida et al, 2022).…”
Section: Introductionmentioning
confidence: 99%